Microwave planar bandpass filter with improved upper stopband - Abdullah, Mohd. Shahar (2013)
Ultra wide-band (UWB) is gained by achieving microwaves bandwidth with equal or more than 500 MHz values. Recent studies focus more on the application of this UWB to fulfill user demand especially in telecommunications nowadays who’s concerned about size of tools and the amount of energy usage. These aspects must put into consideration when purchasing tools for various activities in the field. The use of this ultra-high bandwidth could easily expose to harmonic existence at high frequency which could lead to degradation of systems performance. Thus this project would emphasis on the effort of designing and improving existing microwave bandpass filter based on previous works that could overcome the issue in its first harmonic. Technique chooses include a various flaws form at the back of microstrip planar. All filters have been simulated and the results have been reviewed. In conclusion, frequency at the first harmonic can be reduced in order to improve interference dismissal at high frequency.